The physiologic and phenotypic significance of variation in human amylase gene copy number. Issue 4 (18th September 2018) - Atkinson, Fiona S; Hancock, Dale; Petocz, Peter; Brand-Miller, Jennie C
Abstract: Background: Salivary α-amylase gene ( AMY1 ) copy number (CN) correlates with the amount of salivary α-amylase, but beyond this, the physiologic significance is uncertain. Objective: We hypothesized that individuals with higher AMY1 CN would digest starchy foods faster and show higher postprandial responses and lower breath hydrogen excretion compared with those with low CN. Design: Four linked studies were conducted. In Study 1, we genotyped 201 healthy subjects with the use of real-time quantitative polymerase chain reaction and determined glucose tolerance, insulin sensitivity, salivary α-amylase activity, body mass index (BMI), and macronutrient intake. In Study 2, a pool of 114 subjects tested 6 starchy foods, 3 sugary foods, 1 mixed meal, and 2 reference glucose solutions, containing either 50 or 25 g of available carbohydrate. In Study 3, we compared glycemic and insulin responses to starchy foods with responses to glucose in 40 individuals at extremes of high and low CN. In Study 4, we compared breath hydrogen and methane responses over 8 h in 30 individuals at extremes of CN. Results: AMY1 CN correlated positively with salivary α-amylase activity ( r  = 0.62, P  < 0.0001, n  = 201) but not with BMI, glucose tolerance, or insulin sensitivity. However, CN was strongly correlated with normalized glycemic responses to all starchy foods (explaining 26–61% of interindividual variation), but not to sucrose or fruit. Individuals in the highest compared with the lowest decile of CN produced modestly higher glycemia (+15%, P  = 0.018), but not insulinemia, after consuming 2 starchy foods. Low-CN individuals displayed >6-fold higher breath methane levels in the fasting state and after starch ingestion than high-CN individuals ( P  = 0.001), whereas hydrogen excretion was similar. Conclusions: Starchy foods are digested faster and produce higher postprandial glycemia in individuals with high AMY1 CN. In contrast, having low CN is associated with colonic methane production. This trial was registered at www.anzctr.org.au as ACTRN12617000670370.